PENGARUH PAJAK DAN ZAKAT TERHADAP KONSUMSI DI INDONESIA - Shitny Dwi Istiasih; Munawar (Islamic Economics and finance in Focus, 2022)
This study aims to determine whether there is an effect of taxes and zakat on consumption in Indonesia. This study uses secondary Time Series data during the observation period, namely 2001-2020 in quarterly form. Based on the results of the analysis, it can be concluded that the income variable has a significant effect on consumption in Indonesia in the long and short term. Furthermore, the tax variable shows significant results in the long term and has no significant effect in the short term. Meanwhile, the zakat variable does not show an effect on consumption. There are several allegations that the zakat variable is not significant to consumption, namely 1) the neutralization of the total effect of zakat and 2) caused by the small number of zakat collection and distribution. In this study it can be suggested that the government, optimizing the collection of taxes and zakat can be further strengthened. For example, reporting and evaluation on zakat, the importance of integrated reporting is due to the lack of public trust in paying zakat through institutions.